A prospective evaluation of C-peptide levels and colorectal adenoma incidence. Issue 2 (April 2015) - Murphy, Neil; Cross, Amanda J.; Huang, Wen-Yi; Rajabzadeh-Heshejin, Vian; Stanczyk, Frank; Hayes, Richard; Gunter, Marc J.
Highlights Higher insulin levels have been associated with greater colorectal cancer risk. Whether insulin is similarly related to colorectal adenomas (colorectal cancer precursors) is unclear. We prospectively examined the relationship between C-peptide levels (a marker of insulin) and colorectal adenoma. No relationship between C-peptide and colorectal adenoma was observed. Our results suggest that non-insulin related molecular pathways may be more relevant to early stages of colorectal tumorigenesis.